2009
DOI: 10.1021/om801145v
|View full text |Cite
|
Sign up to set email alerts
|

Can a Butadiene-Based Architecture Compete with its Biaryl Counterpart in Asymmetric Catalysis? Enantiopure Me-CATPHOS, a Remarkably Efficient Ligand for Asymmetric Hydrogenation

Abstract: The double Diels-Alder cycloaddition between 9-methylanthracene and 1,4-bis(diphenylphosphinoyl)buta-1,3-diyne affords the oxide of the atropos diphosphine, Me-CATPHOS, which has an unusual bicyclic buta-1,3-diene-based architecture. Quantum chemical methods using DTF reveal that the barrier to atropinterconversion in Me-CATPHOS is 130 kJ mol -1 , while the corresponding barrier for its unsubstituted counterpart is only 23 kJ mol -1 , entirely consistent with the former being an atropos diphosphine while the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 92 publications
0
9
0
2
Order By: Relevance
“…Gratifyingly, in addition to being an architectural analog of biaryl diphosphines, our preliminary studies revealed Me 2 -CATPHOS to be a highly efficient ligand for the rhodium-catalyzed asymmetric hydrogenation of a range of dehydroamino acid derivatives, as well as (E)-β-aryl-(enamido)phosphonates, in some cases giving ee values in excess of 99%, and in all cases showing a significant enhancement compared with 1; in fact, the ee values obtained for the latter substrates are the highest to be reported 47,48 . Lewis acid platinum-group metal complexes of (S)-Me 2 -CATPHOS also catalyze the carbonyl-ene reaction, and although catalyst performance is substrate-and metal-specific ee values that matched those achieved with 1 were obtained for selected substrates 49 .…”
Section: Simon Doherty and Catherine H Smythmentioning
confidence: 85%
See 2 more Smart Citations
“…Gratifyingly, in addition to being an architectural analog of biaryl diphosphines, our preliminary studies revealed Me 2 -CATPHOS to be a highly efficient ligand for the rhodium-catalyzed asymmetric hydrogenation of a range of dehydroamino acid derivatives, as well as (E)-β-aryl-(enamido)phosphonates, in some cases giving ee values in excess of 99%, and in all cases showing a significant enhancement compared with 1; in fact, the ee values obtained for the latter substrates are the highest to be reported 47,48 . Lewis acid platinum-group metal complexes of (S)-Me 2 -CATPHOS also catalyze the carbonyl-ene reaction, and although catalyst performance is substrate-and metal-specific ee values that matched those achieved with 1 were obtained for selected substrates 49 .…”
Section: Simon Doherty and Catherine H Smythmentioning
confidence: 85%
“…2), which is structurally similar to the biaryl diphosphines in that two diphenylphosphino groups are connected by an unsaturated tether, albeit not a biaryl fragment but an anthracene-derived bicyclic buta-1,3-diene-based framework 46,47 . Key features of Me 2 -CATPHOS (The prefix in the CATPHOS nomenclature/acronym is used to specify the substituents on bridgehead carbon atoms attached to C2 and C3 of the buta-1,3-diene tether.)…”
Section: Simon Doherty and Catherine H Smythmentioning
confidence: 99%
See 1 more Smart Citation
“…Enantiopure Catphos 105b, obtained after fractional crystallization using a tartaric acid derivative, was recently used as ligand in the Rh-catalyzed hydrogenation reactions [64]. With [Rh(COD) 2 ][BF 4 ] (1 mol%) and 105b (1.1 mol%), excellent results were obtained with methyl-2-acetamidoacrylate (98% yield and >99% ee).…”
Section: "In Situ" Formed Alkenylphosphine Complexesmentioning
confidence: 99%
“…[8,9] Zusamenfassend haben wir die spannungsvermittelte [19] chiralen molekulare Magneten, [20] chiralen Speichereinheiten [21] oder als neuartige atropisomere Dien-Liganden für die asymmetrische Katalyse. [22] Eingegangen am …”
unclassified